Design, Synthesis and Pharmacological Evaluation of Novel Imidazopyridine Analogues as Proton Pump Antagonist - Sonawane, Ravindra S.; Patil, Kiran D.; Patil, Avinash V. (Asian Journal of Chemistry, 2020)
A series of novel imidazopyridine derivatives as proton pump inhibitors was designed with compounds of CID data base and explored considering AZD0865 as standard. Many compounds were identified and docked in proton pump ATPase pocket (PDB ID: 4ux2). Molecular docking studies revealed that many compounds showed good proton pump ATPase inhibitory activity. The docking poses revealed the interaction of ligands with amino acid. The standard drug AZD0865 had docking score of -7.112302 and displayed interactions with Asn138 and Asp137. A series of novel imidazopyridine derivatives as proton pump inhibitors were docked, synthesized and characterized by IR, NMR, CHN and MS spectral analysis. The target imidazopyridines were prepared from substituted 2-aminonicotinic acid and 2-bromo-1-substituted ethanone. in vitro Studies explained that few compounds exhibited moderate to good proton pump ATPase inhibitory activity in comparison with the reference drugs i.e. AZD0865. Compounds 11 and 12 shown higher activities with the IC50 4.3. Compounds 1, 4, 6, 7, 8, 10 and 13 showed weak anti-ulcer activity with its IC50 5.2, 5.8, 5.5, 5.1, 4.9, 4.6 and 5.9 and positive control AZD0865 shown IC50 2.0.